Nigeria : Publication of Financial Sector Assessment Program Documentation -- Technical Note on Stress Testing. (IMF Staff Country Reports; Country Report ;, 2013)
To assess the financial stability in Nigeria, various stress tests and analytic processes were undertaken jointly by the Nigerian authorities and the Financial Sector Assessment Program (FSAP) team. The exercise included macroeconomic scenario analysis and its transmission into a range of single- and multifactor shocks. The tests covered the entire Nigerian banking system and looked at the short-term horizon, in part because of data constraints. Sensitivity stress tests estimated the impact of changes in individual variables on banks' portfolios.